PENGARUH INFLUENCER MARKETING DAN EMOTIONAL VALUE TERHADAP PURCHASE INTENTION (STUDI PADA PRODUK VIRTUAL BERUPA SKIN PADA GAME MOBILE LEGENDS: BANG BANG) - Mochamad Luqmanul Hakim; Tias Andarini Indarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The development of the online game market is increasfing due to the intensity of internet use and the consumer's need for entertainment. Companies are competing in compete for the market by increasing consumer purchase intentions, one of which is by taking advantage of the presence of influencers and also the emotional value of the consumer. This research has a purpose to determine the influence of influencer marketing and emotional value toward purchase intention. This study used a quantitative research approach, data analysis using the multiple linear regression method with SPSS 25 application. Questionnaires are distributed online to 100 respondents who know Oura and have done Top-up on the Mobile Legends game. It was found in this study that the influencer marketing variable has a significantly positive effect on purchase intention, emotional value also has a significantly positive effect on purchase intention. From this research, Mobile Legend can fill out strategies to increase consumers' purchase intentions through influencers, because Oura as an influencer can provide information that is easy to understand for respondents While the emotional value can increase the purchase intention of Mobile Legends consumers when consumers get the desired Skin.